Correlation of Anemia in Pregnant Women with Stunting Incidence: A Review - Adilah, Lu’ai Hana’; Syafiq, Ahmad; Sukoso, Sukoso (International Journal Labs, 2023)
The prevalence of stunting is still one of the biggest nutritional problems in the world. Around 150.8 million children under five years old were stunted in 2017, or 22.2% of the population. In 2017, more than half (55%) of children under the age of five who had stunting were from Asia, and more than a third were from Africa (39%). North Asia has the biggest percentage (58.7%) of Asia's 83.6 million children under the age of five. From 2005 to 2017, there was a 36.4% annual increase in the prevalence of stunting in toddlers in Indonesia. One of the factors that cause stunting and low birth weight babies (LBW) is pregnant women who experience anemia. Anemia is a condition of decreasing blood hemoglobin concentration due to micronutrient deficiencies, especially iron, which often occurs in the world affecting more than half of the global population. The most susceptible demographics to anemia are children and women at childbearing age. This research uses the study literature review method. The study was conducted using the results of research from 2016 – 2022 regarding the correlation of anemia in pregnant women and stunting. It is known that macronutrients and micronutrients are correlated with the occurrence of stunting and anemia. It is certainly necessary to make efforts to improve health in both pregnant women and children to prevent the occurance of anemia.